Activation of p38 and JNK by ROS Contributes to Deoxybouvardin-Mediated Intrinsic Apoptosis in Oxaliplatin-Sensitive and -Resistant Colorectal Cancer Cells - Si Yeong Seo; Sang Hoon Joo; Seung-On Lee; Goo Yoon; Seung-Sik Cho; Yung Hyun Choi; Jin Woo Park; Jung-Hyun Shim (MDPI AG, 2024)
Colorectal cancer (CRC) remains a global health burden, accounting for almost a million deaths annually. Deoxybouvardin (DB), a non-ribosomal peptide originally isolated from Bouvardia ternifolia, has been reported to possess antitumor activity; however, the detailed mechanisms underlying this anticancer activity have not been elucidated. We investigated the anticancer activity of the cyclic hexapeptide, DB, in human CRC HCT116 cells. Cell viability, evaluated by MTT assay, revealed that DB suppressed the growth of both oxaliplatin (Ox)-resistant HCT116 cells (HCT116-OxR) and Ox-sensitive cells in a concentration- and time-dependent manner. Increased reactive oxygen species (ROS) generation was observed in DB-treated CRC cells, and it induced cell cycle arrest at the G2/M phase by regulating p21, p27, cyclin B1, and cdc2 levels. In addition, Western blot analysis revealed that DB activated the phosphorylation of JNK and p38 MAPK in CRC. Furthermore, mitochondrial membrane potential (MMP) was dysregulated by DB, resulting in cytochrome c release and activation of caspases. Taken together, DB exhibited anticancer activity against both Ox-sensitive and Ox-resistant CRC cells by targeting JNK and p38 MAPK, increasing cellular ROS levels, and disrupting MMP. Thus, DB is a potential therapeutic agent for the treatment of Ox-resistant CRC.